(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The liver ranks second in frequency of injury after the small intestine, due to its thin capsule covering, loose parenchymal structure, and anatomical location. The main cause of complications in liver injuries is massive intra-abdominal bleeding. Following injuries, extensive blood loss and bile leakage pose a life-threatening danger to the victims. Therefore, timely hospitalization, diagnosis, and surgical intervention, as well as the choice of an adequate method of hemostasis, acquire particular importance. At the same time, the surgeon must minimize the risk of severe intra-abdominal complications, the incidence of which reaches 17–33%. In most cases, liver injuries are multiple, combined, and isolated injuries occur less frequently—7–8%. Penetrating liver wounds are observed in 20–27% of cases. Postoperative course in liver injuries is less lethal, reaching up to 12%.